(untitled) (Tribhuvan University Journal of Microbiology, 2022)
Objectives: This study was aimed to produce single cell protein from possible substrate to yield high protein concentration. Methods: All three types of samples viz banana peel, papaya juice and whey were examined for the estimation of protein concentration. The study was carried out in the Microbiological Laboratory of the Department of Microbiology, D.A.V. College, Dhobighat, Lalitpur from October 19, 2019 to November 29, 2019. The fermentation process was carried out at 32℃ for 5 days and physiochemical analysis of medium was performed every 24 hours. After fermentation, the microbial biomass was extracted and protein concentration was estimated colorimetrically by modified Biuret method. Results: Out of three samples, papaya juice had the highest yeast cell count of 136.25×104 cells/ml followed by whey extract producing 124×104 cells/ml and, the least cell was by banana peel of 104×104 cells/ml. The protein concentration was estimated by the modified biuret’s test. The SCP produced from papaya juice was highest with protein concentration of 23.5% followed by whey extract of 22% and, the lowest protein concentration was of SCP produced from banana peel with 16.04%. Conclusion: The result of this study suggests that production of SCP from whey extract is considered best in terms of better yield and low cost.